Media Pembelajaran Sistem Kendali Berbasis Smart Relay Untuk Mahasiswa Program Studi S1 Pendidikan Teknik Elektro Universitas Pendidikan Ganesha Pada Mata Kuliah Sistem Kendali - I Putu Kresna Budi; I Putu Suka Arsa; Wayan Mahardika Prasetya Wiratama (Universitas Pendidikan Ganesha, 2021)
This study aims to make a based Control System Learning Smart Relay determine the feasibility and determine student responses to learning media for Based Control System Learning Smart Relay in the Control System course in the Undiksha Electrical Engineering Education Study Program. This research uses research and development methods Research and Development (R&D). Data collection in this study was carried out using a questionnaire/questionnaire method which was assessed by content experts, media experts, and students. The results obtained: the results of the validation test from media experts got a percentage of 96.20% with very decent qualifications, the results of the material/content expert test got a percentage of 92.31% with very decent qualifications, the results of small group trials with the lowest score 52 from respondents with /classification is very good and the results of the large group test have the lowest score of 41 from respondents with good category/classification. Based on the research results, the based Control System Learning Media is Smart Relay- feasible to use and gets a good response from students in the Control System learning process in the Undiksha Electrical Engineering Education S1 Study Program.